Structure, content and meaning of organizational networks : extending network thinking - Groenewegen, Peter D.; Ferguson, Julie E.; Moser, Christine, 1963-; Mohr, John; Borgatti, Stephen P. (Research in the sociology of organizations ;, 2017)
To better understand how structure, content and meaning are interrelated, there is great potential in conceptualizing mixed structure linkages, where social relations, events, actions and text-based information intersect. This potential is all the more salient in view of the large data flows and analytical tools that researchers can draw on. However, the increasing availability of tools and data seem to outpace theory development. In response to these trends, this volume aims to advance theoretical understanding of how structure, content and meaning are dynamically intertwined, in both online and offline domains. We also explain the methodological implications of such investigations. This volume therefore responds to the need for in-depth analyses studying the theoretical and methodological implications of the assumed unity of network approaches at the intersections of structure, content and meaning. With these analyses, we show promising approaches, provoke debates in the field, and suggest potential future directions.